Multicenter study on satisfaction, stress and working conditions in nursing in Latin American countries - Diana Carolina Tiga-Loza; Anyela Mancilla-Lucumi; Maria Andrea Castro-Bernal; Oscar Javier Vergara-Escobar; Dora Marcela Llanganate-Osorio; Ernesto Gabriel Reimundo Acosta (Universidade de São Paulo, 2024)
Objective: to assess the job satisfaction level, stressors and working conditions of nursing professionals in some Latin American countries during the COVID-19 pandemic. Methods: this is a cross-sectional study of nursing professionals working in hospital, primary care, educational, governmental, research, commercial and independent institutions. An online survey was carried out to assess satisfaction with the Font-Roja instrument, sociodemographic characteristics, stress factors and working conditions. Results: a total of 1,215 workers from Argentina, Colombia, Mexico, Ecuador and Panama participated. The overall satisfaction score was 81.5 (SD:11.6). There was less satisfaction in the dimensions of tension, pressure, extrinsic characteristics and monotony. Increased stress at work (84.3%), workload (81.3%), fear of SARS-CoV-2 (67.7%), uncertainty at work (51.2%) and salary reduction (20.4%) were reported. The work factors related to satisfaction were, as follows: job recommendation, mixed working hours, care work, increased stress, increased workload, salary reduction and purchase of protective equipment. Conclusion: the aspects of job satisfaction most affected during the pandemic were pressure, tension, lack of independence and monotony at work; this satisfaction was reduced due to increased stress and workload, the acquisition of personal protective equipment and a reduction in salary.